Kajian Fisiko-Kimia Buah Jeruk Siam (Citrus nobilis Lour.) pada Perbedaan Tingkat Kematangan Selama Penyimpanan - NI PUTU ARYANTI; COKORDA GEDE ALIT SEMARAJAYA; I MADE SUKEWIJAYA; I NYOMAN RAI (Agrotrop : Journal on Agriculture Science, 2017)
Physico-Chemical Studies of Tangerine (Citrus nobilis Lour.) on the Differences Level of Maturity Fruits during the Storage Period. Tangerine (Citrus nobilis Lour.) is one of the citrus variety developed in Bali because of the high production and preferred by consumers. In Bali, the center of citrus fruit development is in Kerta village, district of Payangan, Gianyar since 2003. The randomized block design with a single factor was used, with 4 treatments of fruit maturity level and 6 replications. The purpose of this study to determine the level of maturity of citrus fruit based on proper skin color of the fruit to be harvested and to determine the effect of maturity based on the skin color of the fruit, the physico-chemical changes of citrus fruit during storage. The harvest stage of the treatment were 217 days after dormancy (Tk1), 231 days after dormancy (Tk2), 245 days after dormancy (Tk3), and 255 days after dormancy (Tk4). The results showed that the highest shrink in diameter was 0,58cm (Tk1) whereas, the highest weight loss subjectly 19,98% (Tk4) and subjectly towards to the highest water content loss, but also subjectly with lowest levels of vitamin C reduction to 11.87% and the highest of total soluble solit (TSS) increase to 3.29 (oBrix). The indicators preferred by the panelist were neutral according to color, flavour, taste and overall appearance. The good storability for citrus at Tk2 with low damage.